PEMBERDAYAAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA - Rahman, Khairul (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
Execution of development countryside failure during the time result countryside still be considered to be by a link run down in governance system which require to get attention in the case of and kesmiskinan development. One of his/its cause is its weakness participate society in development, internal dikarnakan factor (in x'self society itself) and eksternal factor ( what be at outside society self later do not enable society to participate in development. Program development which is pursuant to partsisiapsi socialize perhaps stem from society demand and requirement enabling program will walk better in line with development to be secure and prosperous socialize. To overcome participate society in pemnbangunan countryside is hence needed by a concept " enableness" participate society in development, because enableness is road;street go to participation socialize in development.